Approximate controllability of a second-order neutral stochastic differential equation with state dependent delay: (Article has been withdrawn) - Das, Sanjukta; Pandey, Dwijendra N.; Sukavanam, Nagarajan (Nonlinear Analysis: Modelling and Control, 2016)
In this paper, the existence and uniqueness of mild solution is initially obtained by use of measure of noncompactness and simple growth conditions. Then the conditions for approximate controllability are investigated for the distributed second-order neutral stochastic differential system with respect to the approximate controllability of the corresponding linear system in a Hilbert space. We construct controllability operators by using simple and fundamental assumptions on the system components. We use the lemma, which implies the approximate controllability of the associated linear system. This lemma is also described as a geometrical relation between the range of the operator B and the subspaces Ni⊥, i = 1, 2, 3, associated with sine and cosine operators in L2([0, a], X) and L2([0, a], LQ). Eventually, we show that the reachable set of the stochastic control system lies in the reachable set of its associated linear control system. An example is provided to illustrate the presented theory.
Keywords: approximate controllability; cosine family; state dependent delay; neutral stochastic differential equation; measure of noncompactness